KONSEP SOSIAL POLITIK TAN MALAKA DAN RELEVANSINYA BAGI HAK ASASI MANUSIA - Zulhelmi, Zulhelmi (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2016)
This study aims to describe the socio-political thought of Tan Malaka related to human rights. This study is a qualitative research with a philosophical approach. This research data in the form of a data library that includes the concept of thinking about social and political life of Tan Malaka related to human rights of individuals and communities and the nation. The data is taken from the books as primary and secondary sources. The main data collection is done by reading, understanding and studying the books source. Data is analyzed by flow models adapted from Miles and Huberman (1984) by steps of data reduction, drawing conclusions, and verification until a final conclusion.